PERENCANAAN DAN STRATEGI KOMUNIKASI DALAM MENINGKATKAN ADAPTIFITAS SUMBERDAYA MANUSIA DAN KEUNGGULAN KOMPETITIF LEMBAGA - Iswahyu Pranawukir (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Planning and communication strategies are one of the keys in increasing adaptability in an institution or organization, including Islamic boarding schools. The purpose of this study is to determine the planning and communication strategies in increasing the adaptability of human resources and competitiveness of the Madinatul Qur'an Islamic boarding school in Depok. Through qualitative descriptive method, the results of planning and communication strategies are obtained according to the stages. The planning stage is to formulate the scientific, capacity and character building. The strategy formulation stage produces an aggressive strategy, involving HR target as partners with various stimuly, refresher strategy through social service practices, growth strategy through the development of intellectual, religious, humanist and adaptive character; defensive strategies through interdisciplinary and transdisciplinary training. Furthermore, the stages of personal competence, through improving communication, managerial and business skills, control stages that focus on the uniqueness of tahfidz, the supervision stage, in the form of optimizing the role of HR and the evaluation stage, in order to encourage the sensitivity of HR to technological developments. Lastly is the communication strategy stage. The graduates of Ma'had Aly will be facilitated with a bachelor degree In order to fulfill the stakeholders’ demand.